Healing Grief A Commentary on Seneca's Consolatio ad Marciam - Tutrone, Fabio (CICERO - STUDIES ROMAN THOUGHT RECEPTION OA, 2022)
Is it possible to overcome grief after years of mourning? What should a Roman woman do to regain control of her thoughts? This book - which is the first commentary in English on Seneca's Consolation to Marcia in forty years, with a revision of the Latin text - explores Seneca's answers to these and other existential questions, shedding new light on Seneca's appropriation of the ancient genre of consolation for the sake of Stoic moral therapy.